Current-field diagram of magnetic states of a surface spin valve in a point contact with a single ferromagnetic film - Yanson, I.K.; Balkashin, O.P.; Fisun, V.V.; Yanson, Yu.I.; Naidyuk, Yu.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We present a study of the influence of an external magnetic field H and an electric current I on the spin-valve (SV) effect in point contact between a ferromagnetic thin film (F) and a sharp tip of a nonmagnetic metal (N). To explain our observations, we propose a model of a local surface SV which is formed in such a N/F contact. In this model, a ferromagnetic cluster at the N/F interface plays the role of the free layer in this SV. This cluster exhibits a larger coercive field than the bulk of the ferromagnetic film, presumably due to its nanoscale nature. Finally, we construct a magnetic state diagram of the surface SV as a function of I and H.